Relationships Between Diurnal Changes of Tongue Coating Microbiota and Intestinal Microbiota - Guo, Xiao-jing; Jiang, Tao; Ma, Xu-xiang; Hu, Xiao-juan; Huang, Jing-bin; Cui, Long-tao; Cui, Ji; Yao, Xing-hua; Shi, Yu-lin; Li, Jun; Guo, Zhi-ling; Lou, Jin-di; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
The oral cavity and the intestine are the main distribution locations of human digestive bacteria. Exploring the relationships between the tongue coating and gut microbiota, the influence of the diurnal variations of the tongue coating microbiota on the intestinal microbiota, can provide a reference for the development of the disease diagnosis and monitoring, as well as the medication time. In this work, a total of 40 healthy college students were recruited. We collected their tongue coating microbiota which was collected before and after sleep and fecal microbiota. The diurnal variations of tongue coating microbiota are mainly manifested on the changes in diversity and relative abundance. There are commensal bacteria in the tongue coating and intestines, especially the Prevotella has the higher proportion in both sites. The relative abundance of Prevotella in the tongue coating before sleep has a positive correlation with intestinal Prevotella, the r is 0.322 (P<0.05). Bacteroides in intestine had the most bacteria associated with the tongue coating, and had the highest correlation coefficient with Veillonella in the oral cavity, which was 0.468 (P＜0.01). These results suggest that the abundance of the same flora in the two sites may have a common change trend. The Sourcetracker results show that the proportion of intestinal bacteria sourced from tongue coating is less than 1%. It indicates that oral flora is difficult to colonize in the intestine in healthy people. This will provide a reference for the study on the oral and intestinal microbiota in diseases.